The Implementation of Online Practicum Classes During the Covid-19 Pandemic at Sampoerna University - Indra Pertama Putra; Ifat Ifat; Kushendarsyah Saptaji; Aditiya Harjon; Yheni Mulyaningsih (JOURNAL OF SCIENCE AND APPLIED ENGINEERING, 2022)
The unprecedented Covid-19 pandemic has altered the way educational institutions operate, including Sampoerna University. Distanced learning has been commonly implemented since then. Not only for taught classes but laboratories or practical activities, such as Mechanics of Materials and Machine Shop have also been organized virtually for the undergraduate student in the mechanical engineering study program. Two stages of activities were carried out during the conduct, namely the (1) preparatory stage, where all the teaching materials in the form of videos were prepared, and (2) virtual lab. At the end of the semester, the participating students were asked to fill out a questionnaire to evaluate the entire practicum process. The results revealed that, according to students, teaching and learning activities performed in such a way are quite effective and satisfying. Regardless, based on the survey result, the students expect to have practical activities conducted in person to gain hands-on experience.